Case report: Multidisciplinary collaboration in diagnosis and treatment of child gaucher disease - Zhu, Jianfang; Sun, Yuxiao; Zheng, Weiyan; Wang, Chunlin (Frontiers in Pediatrics, 2023)
Gaucher disease (GD) is an inherited lysosomal storage disease caused by mutations in the glucocerebrosidase gene. The decrease of glucocerebrosidase activity in lysosomes results in the accumulation of its substrate glucocerebroside in the lysosomes of macrophages in organs such as the liver, spleen, bones, lungs, brain and eyes, and the formation of typical storage cells, namely "Gaucher cells", leading to lesions in the affected tissues and organs. Hepatosplenomegaly, bone pain, cytopenia, neurological symptoms, and other systemic manifestations are common in clinical practice. Most pediatric patients have severe symptoms. Early diagnosis and treatment are crucial to improve the curative effect and prognosis. However, due to the low incidence of this disease, multi-system involvement in patients, and diverse clinical manifestations, multidisciplinary teamwork is needed for comprehensive evaluation, diagnosis and treatment. In this study, we reported 2 cases of different types of GD who were diagnosed, treated and followed up by multidisciplinary collaboration in infancy.